Marital Rape dalam Perspektif Hukum Islam dan Hukum Positif Indonesia: Reinterpretasi Hak Seksual dalam Pernikahan - Firmansyah Firmansyah; Muliadi Muliadi; Ferdian Ferdian; Nanta Septia; Illian Hikma (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Marital rape, or forced sexual intercourse within marriage, is a sensitive issue that remains rarely discussed openly, particularly within the framework of classical Islamic law. Traditional fiqh literature often positions sexual relations as the husband’s absolute right, which the wife is obligated to fulfill, and her refusal is frequently labeled as nusyūz (disobedience), with consequences on her legal entitlements. However, in modern contexts, the maqāṣid al-sharī‘ah (higher objectives of Islamic law) approach emphasizes the protection of life, dignity, and bodily autonomy within marital relations. This study aims to examine the concept of marital rape from the perspectives of both classical and contemporary Islamic law, while also comparing it with the provisions of Indonesia’s positive law, particularly Law No. 23 of 2004 on the Elimination of Domestic Violence and Law No. 12 of 2022 on Sexual Violence Crimes. Using a qualitative library research method, the study finds that marital rape contradicts both the ethical foundations of Islamic law and the constitutional principles of national law. Thus, there is an urgent need for reinterpretation of religious texts and stronger law enforcement to ensure justice and protection for women within the institution of marriage.